The design and flow simulation of a power-augmented shroud for urban wind turbine system / Wong Kok Hoe - Wong, Kok Hoe (2013)
The depletion of fossil fuel and the increase of energy demand in the world make renewable energy become an alternative energy source. Among these green energies, the wind energy is one of the popular energy sources since decades ago. Recently, there are small wind turbine developments which are suitable for urban and suburban application. However, the efficiency of the wind turbine is the main concern for all researchers due to the uncertainty of wind speed and direction in urban area. In this paper, a new power augmented shroud integrated with vertical axis wind turbine (VAWT) is introduced. This power augmented shroud is able to improve the performance of the VAWT significantly by increasing the wind speed, channel the flow to better angle of attack for the VAWT and reduce the negative torque of the wind turbine. Hence, it improves the self-starting of the VAWT, and increase the coefficient of power. The numerical method is used to simulate the wind flow for the power augmented shroud with a single bladed NACA 0015 airfoil VAWT by commercial computational fluid dynamic (CFD) software ANSYS FLUENT 14.0. In this 2D simulation, the shear stress transport (SST) k- turbulence model with the sliding mesh method was used with the tip speed ratio of 5.1 for the wind turbine. The result is verified by re-simulate the experiment published by Sandia National Laboratories. The simulation result shows that the new design of power augmented shroud is able the increase the coefficient of power significant for the VAWT which is about 115.56% compare to the bare VAWT. Therefore, for urban area application, this power augmented shroud can solve the low efficiency problem for the VAWT.